A FACTOR ANALYSIS OF SELF-AUTONOMY FOR PROFESSIONAL TEACHER - Prayai, Narulmon; Aeamtussana, Thammachot; Siripantasak, Narisara (RMUTK Journal of Liberal Arts, 2020)
The purpose of this research was to study factor analysis of self-autonomy for professional teacher. The samples of this study were three hundred sixteen for professional teacher of Srinakharinwirot University selected by purposive sampling. This research instrument used for this study was self-autonomy questionnaire with the discrimination ranges from 0.23 to 0.59 and the reliability coefficient of 0.87. The statistical was analyzed by confirmatory factor analysis. The research was measure model of self-autonomy for professional teacher in accordance fit with the empirical data ( =1.22 df=1 p=.26 GFI=1.00 AGFI=0.98 CFI=1.00 RMSEA=0.02 SRMR=0.00). The factor of each, in descending order as follows: know your duty, Think and decide for yourself and emotional Regulation.